Synthesis Strategies and Multi-field Applications of Nanoscale High-Entropy Alloys - Bin Zhang; Qingxue Mu; Ye Pei; Siyu Hu; Shuo Liu; Taolei Sun; Guanbin Gao (Nano-Micro Letters)
Highlights The comprehensive overview of the synthesis of nanoscale high-entropy alloys and the advantages over conventional alloys. The comprehensive overview of the multi-field applications of nanoscale high-entropy alloys and recent cutting-edge research advances. The comprehensively analyses of the challenges and opportunities in high-entropy alloy development and emphasizes the key application trends in nanosizing and multidimensionalization.